BEYOND ILLNESS AND TRAVEL: REFORMULATING THE PRINCIPLE OF REMOVING HARDSHIP IN ISLAMIC FASTING THROUGH MAQĀṢID AL-QURʾĀN - Abyan Afrizal Cholil; Ahmad Musadad; A Mufti Khazin; Baihaqi; Ahmad Muqoffi Nazral Choir (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2026)
Purpose – This study examines the principle of dafʿ al-ḥaraj (removal of hardship) in Q.S. al-Baqarah (2):185 as a basis for determining rukhṣah (legal concessions) in Islamic law. It asks whether illness (marīḍ) and travel (musāfir) constitute exclusive grounds for obtaining rukhṣah, or whether the verse allows consideration of other forms of hardship. Drawing on Aḥmad al-Raysūnī’s perspective on Maqāṣid al-Qurʾān, this study reconstructs the concept of rukhṣah by recognizing actual hardship (ḥaraj) as a relevant consideration while remaining within the Qur’anic normative framework. Methods – This qualitative library research employs a maqāṣidī-hermeneutical approach. Primary sources include the works of Aḥmad al-Raysūnī, al-Shāṭibī, al-Ṭabarī, Ibn Kathīr, and Ibn ʿĀshūr, supplemented by relevant scholarly literature. The analysis combines textual, comparative, and teleological readings of classical interpretations and maqāṣid thought. Findings – The study demonstrates that Q.S. al-Baqarah (2):185 explicitly associates rukhṣah with illness and travel, while the principle of dafʿ al-ḥaraj provides a basis for understanding the rationale for legal concessions in a more contextual manner. Accordingly, the study proposes a reformulation of dafʿ al-ḥaraj through the concept of verifiable hardship (taḥaqquq al-ḥaraj) as a consideration in determining rukhṣah. This approach does not seek to expand the category of rukhṣah without limits, but to ensure that the application of Islamic law remains responsive to actual circumstances without departing from Qur’anic normative boundaries. Aḥmad al-Raysūnī’s Maqāṣid al-Qurʾān perspective further strengthens this framework by connecting the objective of removing hardship with the dynamics of social life. Research contribution/limitations – This study contributes to the development of Qur’an-based legal reasoning by integrating classical exegesis and Maqāṣid al-Qurʾān in reconstructing the concept of concessions for fasting. The study is limited to Q.S. al-Baqarah (2):185; therefore, the application of dafʿ al-ḥaraj to other areas of Islamic law remains beyond its scope. Originality/value – This study proposes an integrative legal-hermeneutical model that brings Qur’anic interpretation into dialogue with Islamic legal reasoning by positioning dafʿ al-ḥaraj as a teleological foundation for understanding rukhṣah.